Media Komunikasi Visual Mini Album Too Shy, Too Blind Band Magnolia Celebration - Hannan Hafizh Rizq (VisArt: Jurnal Seni Rupa dan Design, 2024)
The music industry continues to be a popular form of entertainment today. The urgency of the problem faced in this research is how to create music popularity by utilizing technological advances that make music easily become famous among the public. problem solving plan by designing visual communication on the Magnolia Celebration mini album entitled "Too Shy, Too Blind". For independent bands like Magnolia Celebration, visuals on mini albums are not only a promotional medium, but are also important to highlight their image and build engagement with the audience. This design uses a qualitative descriptive analysis method through interviews with Magnolia Celebration band members, visual music practitioners, as well as secondary data from the internet. The results show that appropriate visual communication helps strengthen the band's identity, convey the musical narrative, and attract the audience. Thus, the importance of mini album visual communication in strengthening the image and audience involvement as well as providing added value to music promotion.